Perilaku Cyberbullying pada Remaja: Ditinjau dari Anger Management dan Pola Asuh Permisif - Moh Aminullah; Rani Yusriany; Marina Yollanda; Srimulyani Imran (Fakultas Psikologi dan Ilmu Sosial Budaya Universitas Islam Indonesia Yogyakarta, 2018)
Cyberbullying has been developed in recent years. It has negative impacts for its victims such as low self esteem, anxiety, and depression. This study aims to examine the relationship between anger management and permissive parenting patterns with cyberbullying behavior in adolescents. The population in this study are adolescents aged 15-18 years who domiciled in Yogyakarta. The number of samples of this study were 122 adolescents. The research method used is quantitative method with scale as data collection tool. Scale used in this research is anger management scale, permissive parenting scale scale, cyberbullying behavior scale. Data analysis used is multiple regression analysis technique. The results of this study show the coefficient value R = 0.688 with p = 0,000 (p <0.01) which means there is a very significant relationship between anger management and permissive parenting patterns with cyberbullying behavior in adolescents and effective contribution of 47.3%. Effective contribution of anger management variable is 38.5% and permissive parenting pattern is 8.8% to cyberbullying behavior